2012
DOI: 10.1590/s0103-64402012000100011
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of gingival recessions in heavy smokers using two surgical techniques: a controlled clinical trial

Abstract: Smokers have small root coverage which is associated with bad vascularity of periodontal tissues. This study evaluated a technique that can increase the blood supply to the periodontal tissues compared with a traditional technique. Twenty heavy smokers (10 males and 10 females) with two bilateral Miller class I gingival recessions received coronally positioned flaps in one side (Control group) and extended flap technique in the other side (Test group). Clinical measurements (probing pocket depth, clinical atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
2
14
0
4
Order By: Relevance
“…In the current study, the higher plasma levels of cotinine, the most important and stable nicotine metabolite in mammalian species , in the nicotine‐treated mice indicated the systemic distribution of nicotine. The cotinine concentration data from nicotine‐treated mice (Nicotine: 306.8 ± 31.3 ng/ml; Stress + Nicotine: 444.1 ± 25.20 ng/ml) are similar to previous data from heavy smokers (400 ng/ml) and from smokers using or not using nicotine replacement therapy (332.6 and 363.3 ng/ml, respectively) . The Nicotine and Stress + Nicotine groups presented a significant difference in cotinine levels despite having received the same nicotine treatment.…”
Section: Discussionsupporting
confidence: 81%
“…In the current study, the higher plasma levels of cotinine, the most important and stable nicotine metabolite in mammalian species , in the nicotine‐treated mice indicated the systemic distribution of nicotine. The cotinine concentration data from nicotine‐treated mice (Nicotine: 306.8 ± 31.3 ng/ml; Stress + Nicotine: 444.1 ± 25.20 ng/ml) are similar to previous data from heavy smokers (400 ng/ml) and from smokers using or not using nicotine replacement therapy (332.6 and 363.3 ng/ml, respectively) . The Nicotine and Stress + Nicotine groups presented a significant difference in cotinine levels despite having received the same nicotine treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Forty‐eight studies (reported in 57 papers) were included in the review, with 20 providing data for meta‐analyses. Nine RCTs had their data reported in two articles each (i.e., according to the follow‐up period or type of data (i.e., clinical or patient‐reported outcomes) .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies evaluated multiple GR, whereas the others single defects. Two studies evaluated exclusively outcomes of smokers (i.e., 10 or more cigarettes per day for >5 years). In addition, the majority of trials followed participants during a short‐term period (6 to 12 months).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reino et al 43 avaliaram vinte fumantes pesados, apresentando duas retrações bilaterais classe I de Miller, que receberam recobrimento radicular pela técnica de retalho posicionado coronalmente de um lado (grupo controle) e pela técnica do retalho estendido no outro lado (grupo teste). Ambas as técnicas tiveram baixo recobrimento radicular (controle: 43,18% e teste: 44,52%).…”
Section: 48unclassified